1977
DOI: 10.5134/175950
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Observations and Experiments on Pair Formation and Related Behaviours of the Apogonid Fish, Apogon Notatus (Houttuyn)

Abstract: Abstract(!) Underwater observations and experiments on pair formation in Apogon notatus were conducted almost every morning in June to July, 1976 in a rocky region north of the Seto Marine Biological Laboratory. (2) Experiments manifested that homing of this fish at least in the rocky region can be referred to the "pharotaxis". But homing in the sandy area remains still unexplained. (3) The usual sex recognition of this fish is thought to be based primarily on the differences in behavioural patterns between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Such a pattern was evident, for example, in an experimental study on cichlids, where translocated individuals returned after as long as 7 days (Hert, 1992). Homing behaviors have been shown also in other species of cardinalfish (Marnane, 2000;Usuki, 1977). In three different species of cardinalfish, Marnane (2000) showed that the spatial distribution of individuals was highly stable.…”
Section: Discussionmentioning
confidence: 80%
“…Such a pattern was evident, for example, in an experimental study on cichlids, where translocated individuals returned after as long as 7 days (Hert, 1992). Homing behaviors have been shown also in other species of cardinalfish (Marnane, 2000;Usuki, 1977). In three different species of cardinalfish, Marnane (2000) showed that the spatial distribution of individuals was highly stable.…”
Section: Discussionmentioning
confidence: 80%
“…Both females and their mates stay away from their territory during the night, when they feed, mainly on small crustaceans, such as copepods, amphipods and decapods. In spite of this temporary absence, the fish return to the same sites every morning (Usuki, 1977).…”
Section: Study Speciesmentioning
confidence: 99%
“…At the peak of the breeding season, most individuals form pairs, while some remain unpaired, forming loose aggregations in midwater. Paired fish are highly site attached (Usuki 1977) and show aggressive behavior against fish approaching the pair (Kuwamura 1983). Spawning and transfering an egg mass to a male take place within a few seconds, and then the male takes several minutes to completely pack the egg mass into his mouth (Kuwamura 1983).…”
Section: General Reproductive Ecologymentioning
confidence: 99%
“…At the beginning of the next breeding season, a followup survey of marked fish was conducted. Since A. notatus shows high site fidelity (Usuki 1977), marked fish that had disappeared from the quadrat and were not subsequently found nearby (within about 10 m of the quadrat) were regarded as having died. On the basis of this assumption, the annual mortality (%) was calculated from the proportion of marked fish that disappeared to all marked fish observed in the quadrat at the beginning of the breeding season in the previous year.…”
Section: Field Observationsmentioning
confidence: 99%